Platelet‐to‐lymphocyte ratio could be a promising prognostic biomarker for survival of colorectal cancer: a systematic review and meta‐analysis. Issue 7 (16th June 2016) - Peng, Hong‐Xin; Lin, Kang; He, Bang‐Shun; Pan, Yu‐Qin; Ying, Hou‐Qun; Hu, Xiu‐Xiu; Xu, Tao; Wang, Shu‐Kui
Abstract : Inflammation is one of the most important causes leading to colorectal carcinogenesis, and inflammatory biomarkers such as the platelet‐to‐lymphocyte ratio (PLR) might predict survival in colorectal cancer (CRC). However, the prognostic value of PLR in CRC patients remains controversial. The prognostic value of PLR was comprehensively analyzed in 12 articles including 3541 CRC patients (10 for overall survival (OS), seven for disease‐free survival (DFS), three for recurrence‐free survival (RFS), and three for cancer‐specific survival (CSS)) in this study. The overall pooled hazard ratios (HRs) of PLR for OS, DFS, and CSS were significant at 1.29 (95% confidence interval, CI = 1.13–1.47, P H = 0.149), 1.43 (95% CI = 1.03–1.97, P H = 0.025), and 1.26 (95% CI = 1.04–1.52, P H = 0.223), respectively. However, there was no evidence of significance for RFS (HR = 1.29, 95% CI = 0.98–1.70, P H = 0.231) in our study. Stratified analyses indicated elevated PLR was a predictor of poor OS (metastatic patients) and DFS (Caucasian population) and was also significantly associated with OS in univariate analysis (HR = 1.35, 95% CI = 1.14–1.60, P H = 0.532) and those only treated surgically (HR = 1.37, 95% CI = 1.10–1.70, P H = 1.080). However, our findings indicated that elevated PLR is a promising prognostic biomarker for colorectal cancer, especially in metastatic Caucasian CRC patients. Abstract : The ratio of platelets to lymphocytes (PLR) can be measured by a simple and inexpensive blood test. This meta‐analysis examined whether elevated PLR could act as a prognostic biomarker to predict survival of colorectal cancer.